Indvandring, offentlig mening og politisk teori - Rostbøll, Christian F (Politik, 2010)
Regarding issues of immigration, there is a sharp contrast between Danish public opinion and public policy on the one hand and liberal political theory on the other hand. This article analyzes whether it is a problem for liberal theory that argues for more open borders to be so far removed from public opinion and vice versa. Considering issues of realism, epistemology, and democracy it is discussed how directly policy-related political theory ought to be.